Synthesis and anticonvulsant activity of 3-arylamino-4-aryl-5-(N-4-chlorophenylthiocarbamido)-1,2,4-thiadiazoles - Srivastava K.; Pandeya S.N. (My University, 2025)
The 3-(4-chlorophenyl)amino-4-(4-chlorophenyl)-5-(N-4-chlorophenylthiocarbam ido)-1,2,4-thiadiazole possesses significant anticonvulsant activity, devoid of side effect, sedation. The 3-(4-chlorophenyl)amino-4-(4-chlorophenyl)-5-(N-4-chlorophenylthiocarbam ido)-1,2,4-thiadiazole possesses significant anticonvulsant activity, devoid of side effect, sedation. © 1993.